IMPLEMENTATION OF A TECHNOLOGY-BASED STORYTELLING METHOD IN ISLAMIC RELIGIOUS EDUCATION TO ENHANCE THE NOBLE CHARACTER - Muhammad Rizky Ramadhan; Saiful Saiful (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to describe the implementation of a technology-based storytelling method in Islamic Religious Education (IRE) learning and its impact on fostering noble character among grade VII students at SMP Negeri 10 Banda Aceh. The research subjects consisted of the IRE teacher, grade VII homeroom teachers, and the school principal, selected through purposive sampling due to their direct involvement in the learning process and character development. This study employed a qualitative case study design. Data were collected through observation, interviews, and documentation, and analysed using the interactive analysis model comprising data reduction, data display, and conclusion drawing. The findings indicate that the storytelling method was implemented systematically through the utilisation of visual media, such as projectors, to present exemplary stories of the Prophet Muhammad (SAW) and other relevant Islamic figures. The integration of technology was proven to enhance students’ attention, motivation, and emotional engagement in understanding moral values. Interviews revealed that students were guided and continuously monitored to practice noble character, while those who had not shown expected behavioural changes received persuasive guidance through additional reinforcement materials. Documentation of attitude assessments showed significant improvement in aspects of politeness, responsibility, discipline, and social awareness. This study concludes that the technology-based storytelling method is effective in supporting the internalisation of noble character values, with teacher creativity and exemplary conduct serving as key factors driving its success.